The effects of sex and hormonal status on the physiological response to acute psychosocial stress - Kajantie, Eero; Phillips, David I.W. (Psychoneuroendocrinology, 2006)
Whether one is male or female is one of the most important determinants of human health. While males are more susceptible to cardiovascular and infectious disease, they are outnumbered by women for many autoimmune disorders, fibromyalgia and chronic pain. Recently, individual differences in the physiological response to stress have emerged as a potentially important risk factor for these disorders. This raises the possibility that sex differences in prevalence of disease could at least in part be explained by sex differences in the nature of the physiological response to stress. In a psychophysiological laboratory, the autonomic nervous system response can be provoked by many different stressors including physical, mental and psychosocial tasks, while the hypothalamic–pituitary–adrenal axis (HPAA) response seems to be more specific to a psychosocial challenge incorporating ego involvement. The responses of both systems to different psychosocial challenges have been subject to extensive research, although in respect of sex differences the HPAA response has probably been more systematically studied. In this review, we focus on sex differences in HPAA and autonomic nervous system responses to acute psychosocial stress. Although some differences are dependent on the stressor used, the responses of both systems show marked and consistent differences according to sex, with the phase of the menstrual cycle, menopausal status and pregnancy having marked effects. Between puberty and menopause, adult women usually show lower HPAA and autonomic responses than men of same age. However, the HPAA response is higher in the luteal phase, when for example poststress free cortisol levels approach those of men. After menopause, there is an increase in sympathoadrenal responsiveness, which is attenuated during oral hormone replacement therapy, with most evidence suggesting that HPAA activity shows the same trends. Interestingly, pregnancy is associated with an attenuated response of the sympathoadrenal and HPAA systems at least as assessed by biochemical stimulation. It is likely that these sex differences in autonomic function are a result of estrogen exposure which attenuates sympathoadrenal responsiveness. The HPAA is however somewhat more complex and evidence now suggests the influence of other modifiers such as arginine vasopressin (AVP) and the regulation of circulating cortisol bioavailability by corticosteroid-binding globulin (CBG). The pronounced and multi-faceted sex differences in stress responsiveness suggest that they are a product of a strong evolutionary pressure. We hypothesise that this has to a great deal been driven by the need to protect the fetus from the adverse effects of maternal stress responses, in particular excess glucocorticoid exposure. Studying this hypothesis may have a fundamental impact on our understanding about how adult health is set during early life and how adult disease could be prevented in men and women.